Efektivitas Penerapan Klausula Baku Pada Manajemen Cafe Plantkringan Jombang Perspektif Hukum Bisnis Islam - Bella Aulia Firnanda; Norma Fitria (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This research aims to analyse the effectiveness of implementing standard clauses in the management of the Jombang Plantkringan cafe from an Islamic business law perspective. This research uses empirical juridical research methods with a conceptual approach, and data collection uses observation, interviews, questionnaires, documentation, and library data. The data obtained was then analysed using inductive and descriptive methods. Based on the research results, it was found that: 1) the effectiveness of the application of standard clauses in the management of Cafe Plantkringan Jombang has been effective. 2) The application of standard clauses in Cafe Plantkringan has not been effective because Cafe Plantkringan has not implemented the principle of Al-Hurriyah (freedom).